Speech rehabilitation in children with cochlear implants using a multisensory (French Cued Speech) or a hearing-focused (Auditory Verbal Therapy) approach - Van Bogaert, Lucie; Machart, Laura; Gerber, Silvain; Lœvenbruck, Hélène; Vilain, Anne; , Consortium EULALIES; Costa, Maud; Gillet-Perret, Estelle; MacLeod, Andrea A. N.; Meloni, Geneviève; Puissant, Clarisse; Rose, Yvan (Frontiers in Human Neuroscience, 2023)
Early exposure to a rich linguistic environment is essential as soon as the diagnosis of deafness is made. Cochlear implantation (CI) allows children to have access to speech perception in their early years. However, it provides only partial acoustic information, which can lead to difficulties in perceiving some phonetic contrasts. This study investigates the contribution of two spoken speech and language rehabilitation approaches to speech perception in children with CI using a lexicality judgment task from the EULALIES battery. Auditory Verbal Therapy (AVT) is an early intervention program that relies on auditory learning to enhance hearing skills in deaf children with CI. French Cued Speech, also called Cued French (CF), is a multisensory communication tool that disambiguates lip reading by adding a manual gesture. In this study, 124 children aged from 60 to 140 months were included: 90 children with typical hearing skills (TH), 9 deaf children with CI who had participated in an AVT program (AVT), 6 deaf children with CI with high Cued French reading skills (CF+), and 19 deaf children with CI with low Cued French reading skills (CF-). Speech perception was assessed using sensitivity (d’) using both the hit and false alarm rates, as defined in signal-detection theory. The results show that children with cochlear implants from the CF- and CF+ groups have significantly lower performance compared to children with typical hearing (TH) (p<.001 and p=.033, respectively). Additionally, children in the AVT group also tended to have lower scores compared to TH children (p=.07). However, exposition to AVT and CF seems to improve speech perception. The scores of the children in the AVT and CF+ groups are closer to typical scores than those of children in the CF- group, as evidenced by a distance measure. Overall, the findings of this study provide evidence for the effectiveness of these two speech and language rehabilitation approaches, and highlight the importance of using a specific approach in addition to a cochlear implant to improve speech perception in children with cochlear implants.